2023
DOI: 10.14348/molcells.2023.2178
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of RNA Deconvolution Methods and Their Application

Abstract: Tumors are surrounded by a variety of tumor microenviron mental cells. Profiling individual cells within the tumor tissues is crucial to characterize the tumor microenvironment and its therapeutic implications. Since singlecell technologies are still not costeffective, scientists have developed many statistical deconvolution methods to delineate cellular characteristics from bulk transcriptome data. Here, we present an overview of 20 deconvolution techniques, including cuttingedge techniques recently establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…To minimize limitations associated with deconvolution analysis, we used heterogenous data sets as basic matrices and a robust method, CIBERSORTx, for the deconvolution analyses. [61][62][63][64] Our study has limitations. Versatility/plasticity of T-cell subsets could lead to misassignment based on gene expression ascertained at a single time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize limitations associated with deconvolution analysis, we used heterogenous data sets as basic matrices and a robust method, CIBERSORTx, for the deconvolution analyses. [61][62][63][64] Our study has limitations. Versatility/plasticity of T-cell subsets could lead to misassignment based on gene expression ascertained at a single time point.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize limitations associated with deconvolution analysis, we used heterogenous data sets as basic matrices and a robust method, CIBERSORTx, for the deconvolution analyses. 61-64…”
Section: Discussionmentioning
confidence: 99%
“…We report the cellular composition and cell type-specific gene expression in lung tissue associated with disease severity in COPD and IPF subjects, extending the single-cell experiment discoveries from a modest sample size (<100 subjects) to a large population cohort (>1000 subjects). We trained a well-established and widely implemented computational RNA-seq deconvolution algorithm, CIBERSORTx [13,19,20], using publicly available scRNA-seq data from control, COPD, and IPF subjects [9]. We found that IPF lung tissues showed the most divergence from control lungs in cellular composition, with eighteen cell types whose abundance score was different from the controls, adjusting for covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Deconvolution is a data analysis method that can be applied to estimate the ratio of cells in a specimen from bulk transcriptome data (Abbas et al ., 2009; Im and Kim, 2023). Bulk transcriptome is affected by distinctive sample conditions (e.g., gene knock out), individual or technical variations, and relative cell subset proportions.…”
Section: Introductionmentioning
confidence: 99%